Role of AMPD1, COL1A1, and COL5A1 genes polymorphism studies in selection in figure skating - Kalinin, A. V.; Klever-Chekunova, O. A.; Chekunov, M. K.; Chekunova, E. M. (Theory and Practice of Physical Culture, 2021)
Objective of the study was to conduct a comparative analysis of the frequency of polymorphic alleles (SNP) of the AMPD1 (rs17602729), COL1A1 (rs1800012), and COL5A1 (rs12722) genes in successful figure skaters and children, who had not previously trained or taken part in sports competitions and were still selected for sports sections.